EFEKTIFITAS PELAKSANAAN FINGER PRINT DI IAIN RADEN FATAH PALEMBANG - Syahir Badruddin (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
Recently, discipline becomes an important thing that becomes the focus of attention in almost all organizations. Some studies even linking discipline with performance that if the level of discipline members of the organization better then the performance will increase. IAIN Raden Fatah Palembang as one of the organizations also see discipline as an important factor that must be considered by all employees and lecturers mainly based on Government Regulation No. 30 1980 which was amended by Government Regulation No. 53 in 2010. Meanwhile, for the Ministry of Religion itself translated back through the Minister of Religion No. 28 in 2013 and again by Decree especially Rector IAIN Raden Fatah regulating the working hours of employees and lecturers. To obtain a report of presence accountable, it is used in the finger print machine IAIN Raden Fatah Palembang. To see the effectiveness of the implementation of these activities, we conducted observations, interviews and documentation as a means of collecting data. And, the resulting data will be analyzed qualitatively and elaborated descriptively. After the stages of research, showed that the application of the rules the government has been running well and supported by adequate facilities. However, not maximal processing, synchronization data and application of punishment and reward led to a lack of effective use of finger prints on the existing units in IAIN Raden Fatah Palembang.